The Noncoding Mutational Landscape of Pancreatic Cancer Reveals Recurrent Somatic Mutations in Enhancer Regions - Hayashi, Akimasa; Ho, Yu-Jui; Makohon-Moore, Alvin P.; Zucker, Amanda; Hong, Jungeui; Umeda, Shigeaki; Karnoub, Elias-Ramzey; Huang, Jinlong; Baez, Priscilla; Kappagantula, Rajya; Melchor, Jerry P.; Park, Wungki; et al. (Cancer research communications, 2025)
While the coding genome of pancreatic cancer has been characterized in detail, features of the noncoding genome remain relatively unexplored. We used whole-genome sequencing to study the coding and noncoding genomes (promoters, enhancers, and noncoding-nonenhancer regions) in two unique patient cohorts. We find that treated cancers have a significantly higher mutational burden than untreated cancers in all four genomic regions. However, the relative proportion of mutations in each region is preserved despite treatment-induced genetic bottlenecks. Compared with other noncoding regions, enhancers have a lower number of mutations/Mb. Enhancers also have a distinct mutational signature with enrichment of SBS39. Enhancer sequences were segregated into conserved and nonconserved regions based on the overlap of predicted orthologous regions in the human and mouse genomes and the conserved regions screened for recurrent somatic mutations. We find that recurrent somatic mutations in conserved enhancer regions largely correspond to those associated with known transcription factors with a role in pancreatic development and cancer, including KLF5 and TP63. Transcriptional expression based on RNA sequencing data of cancers with enhancer mutations showed significantly different levels of expression, most often a loss of expression, compared with cancers without enhancer mutations, suggesting a functional effect. These findings expand our knowledge of the noncoding genome in pancreatic cancer and point to an unexplored role of conserved enhancer mutations for pancreatic cancer as well. Recurrent somatic mutations in enhancer regions that control pancreatic lineage genes represent a previously unrecognized source of genetic alteration in pancreatic cancer.